Classical Article Evaluation of health-related quality of life the women with human papillomavirus-associated lesions of the cervical epithelium - E G Sycheva; N M Nazarova; O V Burmenskaya; V N Prilepskaya (IP Berlin A.V., 2018)
Objective - to evaluate the health-related Quality of life the women with "lesser" abnormalities of cervical epithelium and patients with high grade squamous intraepithelial lesions (HSIL) associated with human papillomavirus (HPV) infection. Materials and methods. The investigation was performed 274 women of reproductive age, divided into two main groups: HPV infection ("lesser" abnormalities 202 patients and with HSIL - 20) and healthy women - 20. All the studied women of health-related quality of life by using the EQ-5D-5L. Results. Revealed a significant reduction in the level of health-related quality of life in the psychological and emotional components of the patients with "lesser" abnormalities of cervical epithelium and patients with HSIL associated with HPV infection (p